Guillain–Barré syndrome and anti-ganglioside antibodies: a clinician-scientist’s journey - YUKI, Nobuhiro (The Japan Academy, 2012)
Guillain–Barré syndrome (GBS) is the most frequent cause of acute flaccid paralysis. Having seen my first GBS patient in 1989, I have since then dedicated my time in research towards understanding the pathogenesis of GBS. Along with several colleagues, we identified IgG autoantibodies against ganglioside GM1 in two patients with GBS subsequent to Campylobacter jejuni enteritis. We proceeded to demonstrate molecular mimicry between GM1 and bacterial lipo-oligosaccharide of C. jejuni isolated from a patient with GBS. Our group then established a disease model for GBS by sensitization with GM1 or GM1-like lipo-oligosaccharide. With this, a new paradigm that carbohydrate mimicry can cause autoimmune disorders was demonstrated, making GBS the first proof of molecular mimicry in autoimmune disease. Patients with Fisher syndrome, characterized by ophthalmoplegia and ataxia, can develop the disease after an infection by C. jejuni. We showed that the genetic polymorphism of C. jejuni sialyltransferase, an enzyme essential to the biosynthesis of ganglioside-like lipo-oligosaccharides determines whether patients develop GBS or Fisher syndrome. This introduces another paradigm that microbial genetic polymorphism can determine the clinical phenotype of human autoimmune diseases. Similarities between the clinical presentation of Fisher syndrome and Bickerstaff brainstem encephalitis have caused debate as to whether they are in fact the same disease. We demonstrated that IgG anti-GQ1b antibodies were common to both, suggesting that they are part of the same disease spectrum. We followed this work by clarifying the nosological relationship between the various clinical presentations within the anti-GQ1b antibody syndrome. In this review, I wanted to share my journey from being a clinician to a clinician-scientist in the hopes of inspiring younger clinicians to follow a similar path.